Blame the victims? Refugees, state capacity, and non-state actor violence. (January 2019) - Böhmelt, Tobias; Bove, Vincenzo; Gleditsch, Kristian Skrede
Existing research argues that refugee inflows may increase the risk of domestic conflict, particularly civil war that, by definition, involves the state as an actor. However, many of the postulated mechanisms linking refugees to a higher risk of such conflict pertain to tensions with locals, which do not necessarily involve any grievances against government authorities. We contend that it is more likely to identify an association between refugees and non-state actor violence, that is, armed violence between organized non-state groups, neither of which pertains to the state. We also claim that the extent to which refugees are associated with a higher likelihood of non-state conflict depends on the capacity of governments to manage and mitigate risks. We report evidence that refugee populations can be linked to an increased risk of non-state conflict, as well as for a mitigating effect of state capacity on the risk of non-state conflicts in the presence of refugees. We do not find a clear effect of refugee populations on civil war, suggesting that the link depends on existing conflict cleavages relevant to mobilizing refugees or locals. Our research helps to shed light on the relevant security consequences of managing refugee populations. Despite the common arguments portraying refugees as security risks in developed countries, the risk of non-state conflict applies primarily to weak states that have been forced to shoulder a disproportionate burden in hosting refugees.